Motility of the left colon in children and adolescents with functional constpation; a retrospective comparison between solid‐state and water‐perfused colonic manometry. Issue 9 (24th July 2018) - Koppen, I. J. N.; Wiklendt, L.; Yacob, D.; Di Lorenzo, C.; Benninga, M. A.; Dinning, P. G.
Abstract: Background: Using water‐perfused (WP) high‐resolution manometry, we recently demonstrated that children with functional constipation (FC) lacked the postprandial increase in distal colonic cyclic motor patterns that was observed in healthy adults. Our aim was to determine if similar results could be detected using a solid‐state (SS) manometry catheter. Methods: We performed a retrospective analysis of 19 children with FC (median age 11.1 years, 58% male) who underwent colonic manometry with a SS catheter (36 sensors, 3 cm apart). Data were compared with previously published data using a WP catheter (36 sensors, 1.5 cm apart) recorded from 18 children with FC (median age 15 years; 28% male). Key Results: The cyclic motor patterns recorded by the SS catheter did not differ from those previously recorded by the WP catheter. There was no detected increase in this activity in response to the meal in either group. Long‐single motor patterns were recorded in most patients (n = 16, 84%) with the SS catheter. The number of these events did not differ from the WP recordings. In the SS data, HAPCs were observed in 4 children prior to the meal, in 5 after the meal. This did not differ significantly from the WP data. Conclusions & Inferences: These data recorded by SS manometry did not differ from WP manometry data. Regardless of the catheter used, both studies revealed an abnormal colonic response to a meal, indicating a pathology which is not related to the catheter used to record these data. Abstract : Colonic manometry is increasingly utilized in the evaluation of intractable constipation in children. We performed a retrospective analysis of solid‐state colonic manometry recordings in constipated children and compared these to previously published water‐perfused data. The data on the colonic postprandial response did not differ between the solid‐state and water‐perfused catheters. Therefore, regardless of the catheter used, an abnormal response to the ingestion of a meal is demonstrated in children with severe functional constipation.